The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4236/ijcm.2014.59070
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of Manual Chest Compression Technique on Atelectasis in Infants: A Randomized Clinical Trial

Abstract: Objectives: To evaluate the effect of manual chest compression (MCC) in the variables of oxygenation, hemodynamic and respiratory effeteness in infants suffering from respiratory diseases with atelectasis. Methods: Controlled clinical trial, in which 38 infants were evaluated, 19 in each study group (group A: atelectasis and group B: control). Data were measured before, immediately after and 10 minutes after the end of the technique's application. Results: The average age was of 5.05 months. There was an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
(15 reference statements)
0
4
0
3
Order By: Relevance
“…Corroborating with Gardengui et al (23) findings, Diniz et al (24), using methods similar to this study, which evaluated the effects of thoracic compression respiratory maneuvers on hemodynamic and respiratory signs of infants with pulmonary atelectasis, observed that chest compression techniques promote increased respiratory rate, signs of respiratory discomfort and decreased peripheral oxygen saturation, once again reinforcing the clinical instability of compressive techniques application and confronting the study of Souza and Moran (16).…”
Section: Discussionmentioning
confidence: 89%
“…Corroborating with Gardengui et al (23) findings, Diniz et al (24), using methods similar to this study, which evaluated the effects of thoracic compression respiratory maneuvers on hemodynamic and respiratory signs of infants with pulmonary atelectasis, observed that chest compression techniques promote increased respiratory rate, signs of respiratory discomfort and decreased peripheral oxygen saturation, once again reinforcing the clinical instability of compressive techniques application and confronting the study of Souza and Moran (16).…”
Section: Discussionmentioning
confidence: 89%
“…Embora já exista todo esse conhecimento científico acerca da fisiologia neonatal e aplicabilidade das manobras de fisioterapia, eram necessários métodos onerosos para avaliação e verificação desses achados no sistema respiratório de recém-nascidos. 4 Desse modo, a monitorização não invasiva, com ênfase na avaliação da parede torácica, proposta neste estudo, tem adquirido relevância nas mais diversas faixas etárias (RICIERI, 2008;PEREIRA et al, 2014;DINIZ et al, 2014;BARAÚNA et al, 2006).…”
Section: Discussionunclassified
“…Entretanto, o método proposto, este artigo articula um modelo, 2D, que se destaca como método avaliativo do compartimento toracoabdominal em situações diversas na neonatologia. Modelos 2Ds já foram propostos por outros experimentos em situações diversas, (RICIERI, 2008;PEREIRA et al, 2014;FREITAS et al, 2007;DINIZ et al, 2014;BARAÚNA et al, 2006), todavia, esse foi o primeiro modelo criado para avaliação automática da área toracoabdominal em recém-nascidos.…”
Section: Discussionunclassified
“…However when hospitalized in a Neonatal Intensive Care Unit while receiving care that optimize their chances of survival, these newborns often do not receive appropriate interactions for their clinical and social development. Therapies such as the respiratory physiotherapy even though intended to reduce complications of prematurity itself and lessen the environmental conditions to which they are exposed can cause changes in physiological and behavioral parameters of preterm infants 12,13 . Although some studies investigated the behavioral and physiological responses to music on infants [1][2][3][4][5][6] , only a few published reports supported the use of music with premature infants during respiratory physiotherapy 2 , therefore the objective was to evaluate the effects of music on vital signs of preterm infants undergoing respiratory physiotherapy.…”
Section: Introductionmentioning
confidence: 99%